Is POJK No.77/2016 Still Under Start-Up Financing during the Covid-19 Pandemic? - Marwin Antonius Rejeki Silalahi (Almana : Jurnal Manajemen dan Bisnis, 2023)
This scientific article is related to the condition of startup financing and banking in Indonesia. It is linked to the Covid-19 pandemic, which has affected economic conditions in Indonesia, especially MSMEs. This research was conducted solely to determine whether, during the Covid-19 pandemic, the condition of MSMEs (Micro, Small, and Medium Enterprises), which continued to decrease, was still supported by banking institutions and startup financing in Indonesia. This can be analyzed using Strengths, Weaknesses, Opportunities, and Threats. This research provides empirical evidence based on secondary data from trusted institutions in Indonesia. This research looks at two parties, namely internal companies and external parties, namely the Government of Indonesia, which is linked through POJK No. 77 / POJK.01 / 2016. Based on the SWOT analysis, namely Strengths, Weaknesses, Opportunities, and Threats, it can be concluded that cooperation between Fintech Startups and banking institutions has an effect like a knife with a sharp tip and a strong base, where both parties can harm each other. However, this impact can also be mutually beneficial for both parties, if supported by government policies that are in the middle between MSME Startup Fintech and banking institutions and unstable conditions due to the Covid-1 pandemic.